Building Self-Efficacy in Intercultural Communication: A Narrative Study of an International Ph.D Student in The US - Septiani, Putri Tiara; Khafidhoh, Popon Nur; Mahaputri, Ratna Andhika; Herlina, Herlina (Universitas Pendidikan Mandalika, 2025)
This study aims to explore how self-efficacy in intercultural communication was constructed by an Indonesian Ph.D. student in the United States through academic and social experiences. A narrative inquiry design was employed to capture lived experiences and meaning-making processes in intercultural adaptation. Data were collected through in-depth interviews, self-recorded conversations, and researcher notes, with triangulation applied to ensure validity. Thematic analysis indicated that intercultural challenges, including communication barriers and cultural differences, were navigated through adaptive strategies, reflective practices, and support from academic and community networks. The findings suggest that self-efficacy is a dynamic process, strengthened through mastery experiences and social reinforcement. This study emphasizes the need for reflective learning opportunities and empathetic institutional support to enhance international students' intercultural competence.